Wpływ wydarzeń sportowych na wizerunek miasta na przykładzie Poznania = The impact of sporting events on the image of the city – Poznań as a case study - Malchrowicz-Mośko, Ewa; Kamel, Marta; Poczta, Joanna (Journal of Education, Health and Sport, 2016)
Malchrowicz-Mośko Ewa, Kamel Marta, Poczta Joanna. Wpływ wydarzeń sportowych na wizerunek miasta na przykładzie Poznania = The impact of sporting events on the image of the city – Poznań as a case study. Journal of Education, Health and Sport. 2016;6(4):211-232. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.50118 http://ojs.ukw.edu.pl/index.php/johs/article/view/3464 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.03.2016. Revised 17.04.2016. Accepted: 17.04.2016. Wpływ wydarzeń sportowych na wizerunek miasta na przykładzie Poznania The impact of sporting events on the image of the city – Poznań as a case study Ewa Malchrowicz-Mośko, Marta Kamel, Joanna Poczta Wydział Turystyki i Rekreacji AWF w Poznaniu Słowa kluczowe: event, wydarzenie sportowe, wizerunek destynacji turystycznej Key words: event, sporting event, image, tourist destination image Streszczenie: Celem artykułu jest ukazanie wpływu wydarzeń sportowych na kształtowanie pozytywnego wizerunku destynacji turystycznej miasta. Rozważania teoretyczne zostały poparte badaniami empirycznymi przeprowadzonymi podczas trzech wydarzeń sportowych, które odbyły się w Poznaniu. W części teoretycznej opracowania określono pojęcie wydarzenia sportowego i wizerunku destynacji turystycznej oraz ukazano wpływ wydarzeń sportowych na wizerunek miasta w oparciu o analizę literatury przedmiotu. W czwartym podrozdziale zaprezentowano wyniki badań empirycznych, z których wynika, że organizacja wydarzeń sportowych sprzyja kształtowaniu pozytywnego wizerunku miasta. Abstract: The main goal of this article is to show the impact of sporting events on the creation of a positive image of a tourist destination city. Theoretical considerations have been supported by empirical research carried out during the three sporting events that took place in Poznan. In the theoretical part of this work Authors have defined a concept of a sporting event, the image of a tourist destination and the impact of sports events shown on the image of the city based on the literature analysis. The fourth section of this article presents the results of empirical research, which shows that the organization of sporting events is conducive to creating a positive image of the city.